Are Double/Multiple Degree Programs Leading to “Discount Degrees”? - Knight, Jane (International Higher Education, 2015)
The growth in double/multiple degree programs around the world, especially in Europe and Asia, is unprecedented. While the benefits for both students and institutions are many, there is increasing concern about the integrity and legitimacy of those programs which double count credits for two or more qualifications. Challenging questions about the quality assurance, accreditation, recognition an ethics of double/multiple degree programs are posed.